Election Results Prediction Using Twitter Data by Applying NLP - Tripathi, Mukesh Kumar; Neelakantappa, M. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
With the ability to predict political outcomes and provide insights into public opinion, the use of Twitter data to predict election results has gained popularity. Twitter offers a massive supply of data for analysis due to its enormous user base and real-time nature. To categorize tweets as good, negative, or neutral and to follow sentiment patterns over time, researchers use sentiment analysis tools. Network analysis finds influential users and digs deeper into the dynamics of political discourse. The accuracy of predictions is improved by combining traditional polling data with machine learning methods. Twitter data analysis has the potential to offer insightful information for election campaigns and improve political strategies, despite issues like representativeness and identifying genuine sentiment. Ongoing research focuses on refining methodologies and addressing limitations, advancing the reliability of election prediction using Twitter data.